Pendampingan Syawir sebagai Metode Pembelajaran Kitab Kuning di Pondok Pesantren Hidayatul Mubtadi’in Kembang Kabupaten Malang - Arifin, Zainul; Muhammad Adityawarman Fauzi; Ahmad Salsabil Al-Firdausi; Mochammad Soleh; Nilna Rizqiyah; Abidatul Khasanah; Siti Khumaidah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Abstract The Syawir learning method in Islamic boarding schools discusses many aspects of life and worship by referring to the yellow book. In the midst of changing times and technology, problems arise that require adaptation in aspects of life and worship. Integrated mentoring in the program KKN STAI Ma'had Aly Al-Hikam Malang conducted an investigation at the Hidayatul Mubtadiin Kembang Islamic Boarding School, focusing on the students' understanding and soft skills of the yellow book. Investigations show that some students do not understand this aspect. The shawir method is applied to improve students' understanding and soft skills with a program that involves preparation, implementation and evaluation. The target of the program is students in grades 1 and 3 of the Ulya Hidayatul Mubtadiin Kembang Islamic Boarding School. Research methods use observation, interviews, discussions and documentation. The results of the syawir method assistance are increasing understanding of the yellow book and developing students' soft skills, creating sustainable solutions to problems in the Islamic boarding school context. Keywords: Syawir, Method, Learning. Abstrak Metode pembelajaran syawir dalam pesantren banyak membahas aspek kehidupan dan peribadatan dengan merujuk pada kitab kuning. Di tengah perubahan zaman dan teknologi, muncul problematika yang membutuhkan adaptasi pada aspek kehidupan dan peribadatan. Pendampingan yang terintergrasi dalam program Kuliah Kerja Nyata (KKN) STAI Ma’had Aly Al-Hikam Malang ini melakukan investigasi di Pondok Pesantren Hidayatul Mubtadiin Kembang, dengan fokus pada pemahaman dan softskill santri terhadap kitab kuning. Investigasi menunjukkan sebagian santri kurang memahami aspek tersebut. Metode syawir diterapkan untuk meningkatkan pemahaman dan softskill santri dengan program yang melibatkan persiapan, pelaksanaan, dan evaluasi. Sasaran program adalah santri kelas 1 dan 3 Ulya Pondok Pesantren Hidayatul Mubtadiin Kembang. Hasil pendampingan metode syawir adalah meningkatkan pemahaman kitab kuning dan mengembangkan softskill santri, menciptakan solusi berkelanjutan untuk problematika dalam konteks pesantren. Kata kunci: Syawir, Metode, Pembelajaran.